1993
DOI: 10.1093/oxfordjournals.annonc.a058621
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-etoposide and carboplatin-etoposide induction chemotherapy for good-risk patients with germ cell tumor

Abstract: The study suggests that carboplatin-etoposide combination therapy is inferior to cisplatin-etoposide in patients with good-risk germ cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Grade IV neutropenia occurred in 36% of treatment cycles, thus was similar to the degree of neutropenia in the study of Horwich et al [10]. Grade III or IV thrombocytopenia in our study occurred in 16% as compared to 17% in the study of Horwich et al and 0% in another study using etoposide and carboplatin alone, where an insufficient dose of carboplatin was used [12]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Grade IV neutropenia occurred in 36% of treatment cycles, thus was similar to the degree of neutropenia in the study of Horwich et al [10]. Grade III or IV thrombocytopenia in our study occurred in 16% as compared to 17% in the study of Horwich et al and 0% in another study using etoposide and carboplatin alone, where an insufficient dose of carboplatin was used [12]. …”
Section: Discussionsupporting
confidence: 87%
“…In 1989 Horwich et al reported on the effectiveness of carboplatin alone in seminomatous germ cell tumors [9]and in 1991 the same authors reported on the tolerance and favorable outcome of four cycles of carboplatin, etoposide and bleomycin (CEB 90 regimen) in low-risk nonseminomatous germ cell tumors [10]. Two years later it became evident that carboplatin was inferior to cisplatin; however, in both randomized studies bleomycin was omitted and treatments were given at intervals of 4 weeks [11, 12]. Because of the results published by Horwich and colleagues [7], we decided in 1991 to develop a treatment protocol of CEB 90 for patients with low-risk tumors, defined as seminomatous disease and/or nonseminomatous disease with a tumor mass <10 cm, less than 20 lung metastases, no liver, bone or CNS metastases, and levels of AFP <1,000 IU/ml and βHCG <10,000 IU/l, a slight modification of the MRC classification.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its more favourable toxicity profile, carboplatin should not be routinely used in the treatment of testicular GCTs. Several randomized trials have demonstrated an inferior outcome with carboplatin [12][13][14]. Another approach that has been used with some success is to hydrate the patients during cisplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In adult men with testicular cancer, five randomized trials reported superiority of cisplatin over carboplatin. [43][44][45][46][47] Is important to note two major differences between the adult and pediatric carboplatin-based regimens. First, in pediatric trials, the dose-intensity (individual dose and number of cycles) was significantly higher when compared with adult trials, and second, the risk stratification between pediatric and adult patients (and therefore the treatment intensity) was not comparable.…”
Section: Treatment Differences Across Age Groupsmentioning
confidence: 99%